PKM Sosialisasi dan Implementasi Aplikasi “Tentang Anak” untuk Pencegahan Kekurangan Gizi pada Ibu Hamil dan Anak Usia Dini di Posyandu Balita Dusun Kendal Alastengah Paiton - Ahmad Hudawi AS; Dimas Ilham Maulana Asmarakandi; Muhammad Afandi (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
Posyandu Balita in Kendal Paiton Hamlet has a strategic role in improving the health of pregnant women and early childhood, amidst the problem of malnutrition that is often experienced by pregnant women, especially in developing countries. Malnutrition, including chronic energy deficiency (CED), is at risk of increasing long-term health problems such as stunting which affects the quality of Human Resources (HR) in the future. The purpose of this study was to determine the effect of the Student Creativity Program (PKM) activities in increasing the knowledge and awareness of pregnant women in Kendal Paiton Hamlet regarding the importance of fulfilling nutrition during pregnancy and its impact on preventing stunting. This study used a method used to provide socialization and training in understanding applications about children using a pretest-posttest to measure changes in respondents' knowledge and attitudes before and after participating in PKM activities. The pretest results showed that pregnant women's knowledge about nutrition and stunting was relatively low, with an average score of 45%. After participating in PKM activities, in the posttest, the average score increased to 75%, indicating a significant increase in pregnant women's understanding of the importance of balanced nutrition to prevent stunting. Based on these results, it can be concluded that the PKM activity has succeeded in increasing the knowledge and awareness of pregnant women in Kendal Paiton Hamlet regarding nutrition and stunting problems, which are expected to have a positive impact on maternal and child health in the future.